Design of natural asphalt sulfamic acid (NA-NHSO3H) as a scalable natural asphalt-derived heterogeneous Brønsted acid to catalyze multicomponent reactions meeting green chemistry goals - Sahar Abdolahi; Mohammad Soleiman-Beigi (Heliyon)
This study highlights an innovative approach to catalysis by utilizing natural asphalt as a support material for developing carbon-based catalysts. By leveraging the principles of green chemistry, the research aims to create recyclable and environmentally friendly heterogeneous catalytic systems. This aligns with the growing demand for greener technologies and the use of biocompatible materials in chemical processes. Natural asphalt (NA), being a sustainable resource, can potentially reduce the environmental impact associated with traditional catalytic materials. The development of Brønsted acid catalysts on this platform could enhance catalytic efficiency while promoting sustainability. By focusing on recyclable systems, the study also addresses the issue of waste generation in catalytic processes, further advancing the goals of green chemistry. Herein, highlights the emerging role of solid Brønsted acid catalysts (SBACs) in organic synthesis, focusing on a new catalyst known as NA-NHSO3H, which is based on natural asphalt. The synthesis of NA-NHSO3H is straightforward, and its characterization is comprehensively conducted using various analytical techniques such as Fourier transform-infrared spectroscopy (FT-IR), Scanning electron microscopy (SEM), Energy-dispersive X-ray -Map (EDX-Map), Brunauer-Emmett-Teller (BET), Thermogravimetric analysis (TGA) and Transmission electron microscopy (TEM). The catalyst demonstrates high efficacy in the synthesis of a range of heterocyclic compounds, showcasing yields that vary from good to excellent even under environmentally friendly conditions. One of the significant advantages of NA-NHSO3H is its easy separation and reusability, making it economical and aligned with green chemistry principles. Furthermore, the study mentions the practical applicability of this catalyst, evidenced by tests confirming its robustness in gram-scale reactions and through hot filtration tests.